Epidemiology and Outcome of Ankylosing Spondylitis in Northern Norway - Bakland, Gunnstein (University of Tromsø, 2012)
The papers of this thesis are not available in Munin: 1. Gunnstein Bakland1, Hans C. Nossent and Jan T. Gran: 'Incidence and prevalence of Ankylosing Spondylitis in Northern Norway', Arthritis & Rheumatism (2005), vol. 15;53(6):850-5. Available at http://dx.doi.org/10.1002/art.21577 2. Gunnstein Bakland, Jan T. Gran, Andrea Becker-Merok, Bjørn Y. Nordvåg and Johannes C. Nossent: 'Work Disability in patients with Ankylosing Spondylitis in Norway', The Journal of Rheumatology (2011), vol.38 no.3:479-484. Available at http://dx.doi.org/10.3899/jrheum.100686 3. Gunnstein Bakland, Jan Tore Gran and Johannes C Nossent: 'Increased mortality in ankylosing spondylitis is related to disease activity', Annals of the rheumatic diseases (2011), 70(11):1921-5. Available at http://dx.doi.org/10.1136/ard.2011.151191